Sosialisasi Keterlibatan Keluarga Untuk Meningkatkan Keterampilan Personal Menstrual Hygiene di Darul Hukumaini, Jonggat - Rosyunita; Rahmah Dara Ayunda; Lale Justin Elizar; Nurmi Hasbi; Adelia Riezka Rahim (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Adolescence is a transitional period from childhood to adulthood during which physical, psychological, and reproductive changes occur. Menstruation is one of the reproductive changes, and family members or other knowledgeable individuals would ideally support it during this process. This community service activity was designed to educate female students about the role of family in the menstrual process and give them accurate information. This service's method began with a questionnaire, followed by a socialization session led by a speaker, and ended with a discussion. Thirty-two female students, ages sixteen to seventeen, participated in this program. Mothers were chosen by 13, 15, 21, and 13 students, respectively, as the main source of information on menstruation, menstrual hygiene, the use of sanitary pads, and the best source of menstrual education, according to the questionnaire replies. The majority of students reported using disposable sanitary pads. It is anticipated that by improving their knowledge and abilities about menstrual personal hygiene, students would contribute to the development of a healthier generation.